The birds of Batam and Bintan Islands, Riau Archipelago - Rajathurai, Subaraj (KUKILA, 1996)
During 1989 and 1991, ornithological surveys were made on Batam by teams from the Nature Society (Singapore) with the purpose of checking which species remain and also to observe sea birds from the ferry. Between February 1994 and November 1995, the author made nine visits to northern Bintan (an area not visited during the 1991 survey) The purpose was to survey the birds and mammals along the north coast in order to identify areas rich in wildlife and potential wildlife corridors prior to resort development. Each visit lasted from one to four days. During June 1995, a group of students from the National University of Singapore made a two-week bird and mammal study in some of the northern Bintan sites previously covered by the author